No effect of menstrual cycle phase and oral contraceptive use on endurance performance in rowers - Vaiksaar, S.; Jürimäe, J.; Mäestu, J.; Purge, P.; Kalytka, S.; Shakhlina, L.; Jürimäe, T. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to examine whether variables commonly used in aerobic exercise testing are influenced by menstrual cycle phases and use of oral contraceptive (OC) in female rowers. Twenty-four eumenorrheic female rowers distinguished on the basis of both menstrual status and athleticism participated in this study and were divided into competitive cyclic athletes (n = 8), recreationally trained cyclic athletes (n = 7), and recreationally trained athletes taking OC pills (ROC; n = 9). Rowers performed 2 incremental tests to voluntary exhaustion on a rowing ergometer during 2 different phases of the menstrual cycle: the follicular phase (FP) and the luteal phase (LP). The study variables were power output (Pa), heart rate (HR), oxygen consumption (VO2), carbon dioxide production (VCO2), minute ventilation (VE), the mean respiratory exchange ratio, and ventilatory equivalents of O2 (VE/VO2) and CO2 (VE/Vco2), which were measured at maximal and at the aerobic-anaerobic transition intensities. In addition, maximal blood lactate (La) values after the test were obtained. When comparing Pa, Vo2, HR, and La values, no significant differences (p > 0.05) between FP and LP at maximal load and at threshold intensity were found in all 3 groups of the rowers studied. However, we observed higher values (p < 0.05) for VE/VCO2 at both intensities in LP compared with FP in the ROC group. In conclusion, sport-specific endurance performance was not influenced by the phase of the normal menstrual cycle and the synthetic menstrual cycle of the OC users in the rowers studied. Therefore, normally menstruating female rowers and female rowers taking OC pills should not be concerned about the timing of their menstrual cycle with regard to optimized sport-specific endurance performance.